PERSPEKTIF SUMBER DAYA MANUSIA DALAM PENGEMBANGAN BADAN USAHA MILIK DAERAH - NFN Ngadi; Ali Yansyah Abdurrahim (Jurnal Kependudukan Indonesia, 2009)
This paper aims to explore the importance of human resources for the development of enterprises in Indonesia. Analysis in this paper is based on secondary data and desk reviews. Data showed that number of public enterprises in Indonesia has been developed rapidly since the early of pelita I, but it was not followed by improved performance of public enterprises. The empiric facts showed that most public enterprises lose money so they burden on the regional development budget. Many factors were associated with low performance of public enterprises such as human resources as the main factors for the performance of the company. Improving human resources can be made through the procurement function, development, compensation, integration and maintenance. Procurement workforce in the public enterprises should be avoided from corruption, manipulation and nepotism, so public enterprises could recruit competent employees. If these functions run properly, public enterprises would be able to obtain the human resources who are competent to improve the performance of public enterprises. Good performance of public enterprises, such as PDAM in Bogar can be a model of corporate development of other enterprises region in Indonesia.Keywords: human resources, public enterprises, company performance